In situ conservation of wild plant species a critical global review of good practices - Heywood, V.H.; Dulloo, Mohammad Ehsan (2005)
The aim of this book is to provide readers with a broad understanding of the concept and methodologies of in situ conservation for target plant species. The book is based upon a global survey, undertaken by the first author, of existing guidelines, methodologies, case studies and other relevant literature on the in situ conservation of plant species, as well as current activities in this area by national and international agencies. This global review was undertaken as part of a UNEP/GEF project (EP/INT/204/GEF) entitled 'Design, Testing and Evaluation of Best Practices for in situ Conservation of Economically Important Wild Species', for which FAO was the executing agency. In preparing the review for publication as a book, we have taken the opportunity to revise the text and add further examples in order to make it suitable for the general reader interested in the subject of in situ conservation of species. We have tried to include examples from as many countries as possible, although much of the work in this area has up until now been undertaken in temperate regions. We have also provided an extensive bibliography which will allow the reader to explore many of the topics covered in the text in more depth. This book is divided into four parts. Part I deals with the concept, approach and actors of species-based in situ conservation and attempts to clarify the ambiguity of the concept of in situ conservation as it relates to target species. In the minds of many people, in situ conservation is taken to mean the creation of protected areas and implies a narrow ecosystem approach, with the inclusion of local communities and conservation of species being incidental. This concept is now rapidly changing, as more focus is placed on individual target species and the needs and well-being of local communities and people are beginning to receive more consideration. It is also clear that in situ conservation cannot be the sole mode of conservation: it will not be possible to turn the location of every population of wild plants into a protected area, due to cost considerations or other land-use reasons. in situ conservation will need to be complemented by ex situ conservation where appropriate and, in particular, some sites will need to be managed with local stakeholders in a participative manner. Global changes in population growth, land-use patterns and climate change will also affect the ways in which in situ sites are designed and managed (see Section 1.5). This part also discusses the most important international instruments which govern the conservation of wild plant species, notably the Convention on Biological Diversity and the Global Plan of Action, as well as other regional initiatives, and the role of major UN and international agencies dealing with wild species. Part II of the book focuses on in situ conservation methodologies and describes the various approaches of in situ conservation and the main steps needed for developing a conservation strategy for target species in situ. A number of initial steps are required before in situ conservation sites can be effectively planned and established. These include setting priorities for target species, establishing an information baseline through the carrying out of ecogeographical surveys, and estimating the amount and pattern of genetic diversity. Once this information becomes available, it is possible to prioritize conservation areas for protection and/or management. This part also describes the different types and the role of protected areas in species conservation, and discusses the conservation of species outside protected areas. Of even more importance is the management and monitoring of in situ conservation and populations: this aspect is one of the most neglected in protected areas management, as many protected areas do not have management plans or are not adequately managed, especially for target species. These issues need to be given more prominence by policy-makers. The global survey of in situ conservation activities is described in Part III. Examples of in situ conservation of various types of taxa, such as threatened species, medicinal and aromatic species, forestry species, crop wild relatives, fruit trees and shrubs, and ornamental and other miscellaneous groups across the world are provided as illustrations of their effective conservation in situ. Detailed information about specific case studies is provided in boxes throughout the text. Finally, Part IV offers some conclusions and recommendations. It is hoped that this book will provide managers of protected areas, conservation officers and government officials, as well as all stakeholders involved in in situ conservation, with valuable information and an in-depth understanding of in situ conservation methodologies. It should also be a valuable guide for students of ecology and others engaged in the study of plant genetic resources.